(untitled) (Quinto Sol, 2020)
After the First World War, an international movement was consolidated with the objective of promoting health reforms. This work analyzes the Youth Red Cross, as one of the organizations that joined the aforementioned movement from a different logic than other organizations. In this case, it is a socio-cultural perspective on the actions of young people in community-based health promotion tasks, paying special attention to participatory methodologies and techniques aimed at disseminating "health education programs" in Latin American societies.